Sistem Informasi Emosional Mental Problems (Siempro) Untuk Meningkatkan Kecakapan Pelayanan Kader Posyandu Balita - Ifalahma, Darah; Arniwati Binti Mat Daud, Noor; Amalya Putri Handayani, Adisty; Siti Zamrina, Nurlaila (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Emotional behavioral problems affect the quality of life and development of children. Early detection is carried out periodically in health services, involving health workers and cadres. Early detection of emotional mental problems has not been optimally carried out in integrated health posts. Many cadres do not yet have the knowledge and skills. Integrated health posts are not yet equipped with valid and easy-to-use early detection instruments. Research has been conducted by the author on the Emotional Mental Problems Information System (Siempro), developed from the Emotional Behavior Problems Questionnaire of the Ministry of Health of the Republic of Indonesia. This information system was tested at one integrated health post in Surakarta, and can be used as a fast-accurate early detection instrument. As a novelty, this study conducted a wider scope experiment. The study aims to determine the effectiveness of using Siempro on cadre skills. Pre-Experimental Design One-Group Pretest-Posttest research design. Representative samples of cadres from 10 integrated health posts in Surakarta, totaling 30 cadres. The instrument uses a questionnaire and checklist, the intervention uses Siempro. Wilcoxon Signed-Rank data analysis. The results of the Wilcoxon Signed-Rank test for the knowledge variable p=0.006, skills p=0.000, duration of early detection p=0.002, and accuracy in determining conclusions p=0.000. All p values ​​<α (0.05), meaning that there is a significant difference between before and after the intervention. Conclusion: The use of Siempro is effective in improving the skills of cadres at the Surakarta City Posyandu. This study produces an instrument for early detection of children's emotional behavior problems that can be used effectively and efficiently.